Individual Characteristics of Caregivers to the Adolescent Girls. Do they Influence Initiation to Human papillomavirus Vaccination? A Cross-sectional Study. - Wangwa, Fred (Student's Journal of Health Research Africa, 2022)
Background Initiation to the HPV vaccine is critical in the prevention of cervical cancer and failure to receive vaccines as recommended may aggravate the disease burden on the female population. Unfortunately, evidence indicates that initiation to HPV vaccination is still very low in Mbale district, Uganda, and sub-Saharan Africa at large. Hence this study is conducted to study the Individual characteristics of Caretakers of the adolescent girls under the care and how they influence the initiation of HPV vaccine aged 9 to 17 years in Mbale District, Eastern Uganda. Methodology: The study adopted a population-based cross-sectional study design in which questionnaires were used in the data collection process. The data were analyzed in STATA. Data was collected from 4th/01/2021 to 20th/05/2022. Results: The Individual factors that had a significant association with initiation to HPV were School Category, gender of caretaker, education level of caretaker, the religion of caretaker, caretaker’s place of residence, and employment category of caretaker. The rest of the variables did not have a statistically significant association with the initiation of HPV. No individual factors influenced the initiation of HPV vaccination after controlling for confounding effects. Conclusion: Individual characteristics play a role in influencing caretakers towards initiation to HPV vaccination when assessed in isolation. Recommendations: Families with cervical cancer history should be encouraged to initiate their adolescent girls to HPV vaccination at the recommended age of 9 years and ensure all the recommended doses are completed as these girls are highly susceptible to cancer.